Marvelous stories from the perfection of wisdom : 130 didactic stories from Arya Nagarjuna's exegesis on the great perfection of wisdom sutra - Nāgārjuna, Arya; Dharmamitra, Bhikshu (Seattle : Kalavinka Press, 2009)
Naast de Engelse vertaling bevat dit boek ook de originele tekst.